Evidence for the impact of BAG3 on electrophysiological activity of primary culture of neonatal cardiomyocytes. Issue 10 (1st April 2019) - Tahrir, Farzaneh G.; Gordon, Jennifer; Feldman, Arthur M.; Cheung, Joseph; Khalili, Kamel; Mohseni Ahooyi, Taha
Abstract: Homeostasis of proteins involved in contractility of individual cardiomyocytes and those coupling adjacent cells is of critical importance as any abnormalities in cardiac electrical conduction may result in cardiac irregular activity and heart failure. Bcl2‐associated athanogene 3 (BAG3) is a stress‐induced protein whose role in stabilizing myofibril proteins as well as protein quality control pathways, especially in the cardiac tissue, has captured much attention. Mutations of BAG3 have been implicated in the pathogenesis of cardiac complications such as dilated cardiomyopathy. In this study, we have used an in vitro model of neonatal rat ventricular cardiomyocytes to investigate potential impacts of BAG3 on electrophysiological activity by employing the microelectrode array (MEA) technology. Our MEA data showed that BAG3 plays an important role in the cardiac signal generation as reduced levels of BAG3 led to lower signal frequency and amplitude. Our analysis also revealed that BAG3 is essential to the signal propagation throughout the myocardium, as the MEA data‐based conduction velocity, connectivity degree, activation time, and synchrony were adversely affected by BAG3 knockdown. Moreover, BAG3 deficiency was demonstrated to be connected with the emergence of independently beating clusters of cardiomyocytes. On the other hand, BAG3 overexpression improved the activity of cardiomyocytes in terms of electrical signal amplitude and connectivity degree. Overall, by providing more in‐depth analyses and characterization of electrophysiological parameters, this study reveals that BAG3 is of critical importance for electrical activity of neonatal cardiomyocytes. Abstract : Connectivity map showing the degree of correlation among different electrodes.